A Genome-Wide Collection of Mos1 Transposon Insertion Mutants for the C. elegans Research Community - Vallin, Elodie; Gallagher, Joseph; Granger, Laure; Martin, Edwige; Belougne, Jérôme; Maurizio, Julien; Duverger, Yohann; Scaglione, Sarah; Borrel, Caroline; Cortier, Elisabeth; Abouzid, Karima; Carre-Pierrat, Maité; et al. (PLOS ONE, 2012)
Methods that use homologous recombination to engineer the genome of C. elegans commonly use strains carrying specific insertions of the heterologous transposon Mos1. A large collection of known Mos1 insertion alleles would therefore be of general interest to the C. elegans research community. We describe here the optimization of a semi-automated methodology for the construction of a substantial collection of Mos1 insertion mutant strains. At peak production, more than 5,000 strains were generated per month. These strains were then subject to molecular analysis, and more than 13,300 Mos1 insertions characterized. In addition to targeting directly more than 4,700 genes, these alleles represent the potential starting point for the engineered deletion of essentially all C. elegans genes and the modification of more than 40% of them. This collection of mutants, generated under the auspices of the European NEMAGENETAG consortium, is publicly available and represents an important research resource.